Vulnerability of grassland seed banks to resource‐enhancing global changes. Issue 12 (8th September 2021) - Eskelinen, Anu; Elwood, Elise; Harrison, Susan; Beyen, Eva; Gremer, Jennifer R.
Abstract: Soil seed banks represent reservoirs of diversity in the soil that may increase resilience of communities to global changes. Two global change factors that can dramatically alter the composition and diversity of aboveground communities are nutrient enrichment and increased rainfall. In a full‐factorial nutrient and rainfall addition experiment in an annual Californian grassland, we asked whether shifts in aboveground composition and diversity were reflected in belowground seed banks. Nutrient and rainfall additions increased exotic and decreased native abundances, while rainfall addition increased exotic richness, both in aboveground communities and seed banks. Under nutrient addition, forbs and short‐statured plants were replaced by grasses and tall‐statured species, both above and below ground, and whole‐community responses to the treatments were similar. Structural equation models indicated that especially nutrient addition effects on seed banks were largely indirect via aboveground communities. However, rainfall addition also had a direct negative effect on native species richness and abundance of species with high specific leaf area (SLA) in seed banks, showing that seed banks are sensitive to the direct effects of temporary increases in rainfall. Our findings highlight the vulnerability of seed banks in annual, resource‐poor grasslands to shifts in compositional and trait changes in aboveground communities and show how invasion of exotics and depletion of natives are critical for these above‐belowground compositional shifts. Our findings suggest that seed banks have limited potential to buffer resource‐poor annual grasslands from the community changes caused by resource enrichment.